Research of energy efficiency direct-heating systems with sequential connection of space heaters with different methods of heat consumption regulation; European Physical Journal Web of Conferences (EPJ Web of Conferences); Vol. 82 : Thermophysical Basis of Energy Technologies - Morozov М. N. Maksim Nikolaevich (2015, 2015)
Title screen